VD_FINDINFO Arrêt / 2010 / 509 vom 22. März 2010 - VD Tribunal cantonal (2010)
RENTE D'INVALIDITÉ, RENTE EXTRAORDINAIRE | 1 LAI, 2 LAI, 29 LAI, 36 al. 2 LAI, 39 al. 1 LAI, 69 al. 1bis LAI, 1 al. 1 LAVS, 29 al. 2 LAVS, 29bis LAVS, 3 LAVS, 42 al. 1 LAVS, 4 LPC, 58 LPGA, 6 LPGA, 60 al. 1 LPGA, 7 LPGA, 117 al. 1 LPA-VD, 49 al. 1 LPA-VD, 55 al. 1 LPA-VD, 93 al. 1 let. a LPA-VD